Laser and vision-based measurements of helicopter blade angles. (March 2018) - Zappa, Emanuele; Liu, Rui; Trainelli, Lorenzo; Ferrario, Andrea; Cordisco, Potito; Terraneo, Mauro; Grassetti, Riccardo; Redaelli, Matteo
Highlights: Novel techniques are proposed, for helicopter blade angles measurement during flight. 2D laser system and vision-based system are developed. All the proposed solutions are fully characterized. Stereo camera system is selected as the best candidate for flight tests. Abstract: In this paper, three novel non-contact measurement systems for helicopter rotor blades, based on the 2D laser triangulation, the single camera and the stereo camera respectively, are designed and developed. The three measurement systems are applied to reconstruct the spatial position of the blade, and consequently its attitude angles. The measuring qualities of the three systems are assessed by means of experiments, including vibration tests, coupled rotation and vibration tests, and accuracy tests with complex motion configurations. These tests demonstrate that the three solutions can perform continuous operation correctly in a relevant dynamic environment. The results of accuracy tests show that, while all the systems can be successfully applied for the measurement of the angles of a helicopter blade, the stereo camera system provides a better accuracy than the other two systems. In particular, for the stereo camera system, the discrepancies of the three angles are comprised between 0.1 and 0.3 degrees in case of realistic blade motion conditions.